Gladys Black letter to Nicholas S. Halmi regarding bird sightings, June 2, 1977 - Black, Gladyset al (1977)
Letter from Gladys Black to Nicholas S. Halmi, regarding bird watching and sightings. Item includes notes on observations by bird type. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1977. Epson - sheet feed/flatbed